A novel 18F-labelled high affinity agent for PET imaging of the translocator protein1. Issue 8 (14th August 2015) - Blair, Adele; Zmuda, Filip; Malviya, Gaurav; Tavares, Adriana A. S.; Tamagnan, Gilles D.; Chalmers, Anthony J.; Dewar, Deborah; Pimlott, Sally L.; Sutherland, Andrew
<x xml:space="preserve">Abstract</x> A novel 18F-labelled quinoline-2-carboxamide has been characterised as a novel PET imaging agent for the translocator protein.